Depression and anxiety in prostate cancer: a systematic review and meta-analysis of prevalence rates. Issue 3 (13th March 2014) - Watts, Sam; Leydon, Geraldine; Birch, Brian; Prescott, Philip; Lai, Lily; Eardley, Susan; Lewith, George
Abstract : Objectives: To systematically review the literature pertaining to the prevalence of depression and anxiety in patients with prostate cancer as a function of treatment stage. Design: Systematic review and meta-analysis. Participants: 4494 patients with prostate cancer from primary research investigations. Primary outcome measure: The prevalence of clinical depression and anxiety in patients with prostate cancer as a function of treatment stage. Results: We identified 27 full journal articles that met the inclusion criteria for entry into the meta-analysis resulting in a pooled sample size of 4494 patients. The meta-analysis of prevalence rates identified pretreatment, on-treatment and post-treatment depression prevalences of 17.27% (95% CI 15.06% to 19.72%), 14.70% (95% CI 11.92% to 17.99%) and 18.44% (95% CI 15.18% to 22.22%), respectively. Pretreatment, on-treatment and post-treatment anxiety prevalences were 27.04% (95% CI 24.26% to 30.01%), 15.09% (95% CI 12.15% to 18.60%) and 18.49% (95% CI 13.81% to 24.31%), respectively. Conclusions: Our findings suggest that the prevalence of depression and anxiety in men with prostate cancer, across the treatment spectrum, is relatively high. In light of the growing emphasis placed on cancer survivorship, we consider that further research within this area is warranted to ensure that psychological distress in patients with prostate cancer is not underdiagnosed and undertreated.